Plasma Activation and its Nanoconfinement Effects Boost Surface Anti‐Biofouling Performance. Issue 6 (16th December 2022) - Mahmoodi, Nasim; Bazzoli, Dario G.; Overton, Tim W.; Mendes, Paula M.
Abstract: Although plasma treatment can alter polymer surface wettability and adhesiveness, scant attention has been given to plasma effects across scales and their anti‐fouling performance. Herein, the discovery that plasma‐activated polydimethylsiloxane (PDMS) nanopillar arrays remarkably enhance anti‐fouling behavior, yielding a 98.7% reduction in Escherichia coli adhesion compared to native planar surfaces. The plasma‐activated nanopillar arrays can hold to their anti‐fouling properties for extended periods of storage, still exhibiting more than 65.1% less bacterial colonization than their native planar counterparts after 50 days. The anti‐fouling behavior promoted by plasma activation is significantly enhanced as the structure features reduce in size from macroscale to microscale to nanoscale, revealing an altered plasma activation effect upon confinement at the nanoscale level. It is anticipated that the findings will improve the ability to achieve non‐fouling effects in polymeric materials for a broad range of applications in clinical and industrial settings. Abstract : Herein, we report our discovery that plasma‐activated polydimethylsiloxane (PDMS) nanopillar arrays remarkably enhance anti‐fouling behavior, yielding a 98.7% reduction in Escherichia coli adhesion compared to native planar surfaces. The plasma‐activated nanopillar arrays can hold to their anti‐fouling properties for extended periods of storage, still exhibiting more than 65.1% less bacterial colonization than their native planar counterparts after 50 days.